Lower and upper bound form for outage probability analysis in two-way of half-duplex relaying network under impact of direct link - Phu Tran Tin; Van-Duc Phan; Tan N. Nguyen (Universitas Ahmad Dahlan, 2021)
In this paper, the system performance of the two-way of half-duplex (HD) relaying network under the impact of the direct link is studied. The model system has two sources (S) and one destination (D) communicate by direct link and via relay (R). For system performance analysis, we derived the lower and upper bound for outage probability (OP). Furthermore, the analytical expressions of the system performance are verified by using the Monte Carlo simulation in the effect of main parameters. As shown in the results, we can the simulation and analytical results have a good agreement.